A Note on Soviet Capital Controversy - Zauberman, Alfred (Quarterly Journal of Economics, 1955)
Journal Article A Note on Soviet Capital Controversy Get access Alfred Zauberman Alfred Zauberman London, England Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 3, August 1955, Pages 445–451, https://doi.org/10.2307/1885850 Published: 01 August 1955